Effects of Artificial Staining and Bleaching Protocols on the Surface Roughness, Color, and Whiteness Changes of an Aged Nanofilled Composite - dos Santos Muniz Mota, Geyse Maria; Kury, Matheus; Pereira da Silva Braga Tenório, Cecília; Lucisano Botelho do Amaral, Flávia; Turssi, Cecília Pedroso; Cavalli, Vanessa (Frontiers in Dental Medicine, 2020)
This study evaluated the surface roughness and color alteration of an aged nanofilled composite exposed to different staining solutions and bleaching agents. Ninety nanofilled composite (Filtek Z350XT, 3M/Oral Care) specimens were submitted to 5,000 thermal cycles and immersed in (n = 30): red wine, coffee, and artificial saliva at 37°C for 48 h. Groups were subdivided according to the bleaching protocol (n = 10) with 20% carbamide peroxide, 38% hydrogen peroxide, or without bleaching - control. Mean surface roughness values (Ra - μm) and color parameters (L*, a*, b*) were measured at baseline (T0), after thermal cycling aging and staining (TS), and after bleaching (TB). Color (ΔE00) and whiteness index (ΔWID) changes were determined after aging and staining (Ts-T0) and after bleaching (TB-TS). The adopted perceptibility and acceptability thresholds of the nanofilled composite were 0.81 and 1.71 ΔE00 units and 0.61 and 2.90 ΔWID units, respectively. Ra was analyzed using mixed models for repeated measurements and L* by the Tukey-Kramer test. The a* and b* values were evaluated by generalized linear models for repeated measures. ΔE00 was tested using two-way ANOVA and Tukey tests, and ΔWID by Kruskal-Wallis and Dunn tests (α = 5%). Ra of all groups decreased after aging and staining (TS, p < 0.05), but increased after bleaching only for groups stained with red wine (TB). Aging and staining decreased the luminosity of the composites, but L* increased after bleaching (p < 0.05). Aging and staining increased a* and b* values, but after bleaching, b* values decreased (p < 0.05). After bleaching, ΔE00 and ΔWID were greater in stained groups at both time intervals, regardless of the bleaching protocol. Stained resin composites exhibited perceptible but unacceptable color (ΔE00 > 1.71) and whiteness (ΔWID > 2.90) changes, regardless of the bleaching treatment performed. Therefore, red wine affected the surface roughness of the aged nanofilled resin submitted to bleaching. Bleaching was unable to reverse the color changes promoted by red wine and coffee on the aged nanofilled composite.